Do religious practices influence compliance behaviour of business zakat among SMEs?/ Mohd. Rahim Khamis ... [et al.] - Khamis, Mohd Rahim; Mohd, Rohani; Md Salleh, Arifin; Nawi, Abdol Samad (Universiti Teknologi MARA, 2014)
Religious value is one of the factors determining compliance behavior of zakat as revealed by a number of studies. However, lack of study focused on religious practices and compliance behavior of zakat especially in the business zakat scenario. Hence, the main objective of this study is to determine whether religious practices influence compliance behavior of business owners towards business zakat. 276 questionnaires managed to be collected from SMEs entrepreneurs in Selangor. Rasch Measurement Model was employed to analyze the data. The construct was found reliable with Cronbach Alpha of 0.98. The statistical indicators such as mean square (MNSQ), Z-standardized (ZSTD), point measure correlation (PtMea Corr) and Person Item Distribution Map (PIDM) revealed that among 276 respondents, 106 respondents who performed religious practices meet the business zakat compliance. Interestingly 132 respondents did not comply with business zakat payment even though they perform business practices. The implication of this paper provides evidence of the usefulness of Rasch Measurement Model in identifying the compliance behavior of zakat payment among businesses. It is also able to explain that religious practices really influence Muslim business community to comply with business zakat payment.